Inclusiveness of citizens' roles in its development through Merdeka Belajar Kampus Merdeka curriculum in higher education - Sari, Wahyuningtyas Nilam; Sutirman, Sutirman (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
Education is the main key to human resource development, enabling individuals to improve their abilities and skills in the formal and non-formal domains, compete, and develop potential in the world of work. However, significant challenges arise for higher education graduates, where some of them experience open unemployment because they have not been fully absorbed in the labor market. This research is focused on the concept of human resource development inclusiveness in the Merdeka Belajar-Kampus Merdeka Curriculum in Indonesian Higher Education. This study used a literature study approach, referring to previously published research. The analysis was conducted to explore the extent of higher education's impact on the open unemployment rate and how changes in curriculum and learning methods could help overcome these challenges. It was hoped that the results of this study could contribute to further understanding of the relationship between higher education and open unemployment, as well as provide insights into solutions that can be implemented to improve the employability of graduates in the labor market.